A lithium sodium composite inorganic sulfide solid electrolyte material and preparation method thereof

By adding Na elements to the lithium-ion solid electrolyte and adjusting the element ratio, a high-ion conductivity lithium-sodium composite inorganic sulfide solid electrolyte material was prepared, which solved the problem of low ionic conductivity of existing materials and realized the application of high-performance all-solid state batteries.

CN117174992BActive Publication Date: 2025-03-28GUOLIAN CORE MATERIALS (BEIJING) TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311022496.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-03-28
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

The existing inorganic sulfide solid electrolyte materials have low ionic conductivity and are difficult to meet the needs of high-performance all-solid state batteries.

Method used

By adding a small amount of Na element to the lithium-ion solid electrolyte, the types and proportions of elements in the inorganic sulfide solid electrolyte material are adjusted, and a variety of different types of lithium-sodium composite inorganic sulfide solid electrolyte materials with solid solution phase structure are obtained. The preparation method of the material includes mixing the raw materials under an inert atmosphere protection and grinding, and then performing heat treatment to improve the ionic conductivity of the material.

Benefits of technology

The ionic conductivity of lithium-sodium composite inorganic sulfide solid electrolyte material has been significantly improved to reach 6.37mS/cm, meeting the application needs of high-performance all-solid state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117174992B_ABST
    Figure CN117174992B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium-ion batteries, and in particular to a lithium-sodium composite inorganic sulfide solid electrolyte material and a preparation method thereof. The composition of the lithium-sodium composite inorganic sulfide solid electrolyte material of the present invention is shown in the following general formula I: Li 7‑i‑k‑ 1Na i P j S k X1(I); wherein X is one or more of F, Cl, Br, and I, 0.0<i<7.0, 0.0<j≤1.0, 3.0<k≤6.5, and 0.0≤1<2.0. A lithium-sodium composite inorganic sulfide solid electrolyte material of the present invention obtains a plurality of different types of lithium-sodium composite inorganic sulfide solid electrolyte materials with solid solution phase structures by adjusting the types and proportions of elements in the material. The lithium-sodium composite inorganic sulfide solid electrolyte material has higher ionic conductivity, and can further realize the application of sulfide solid electrolyte materials in high-performance all-solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium-sodium composite inorganic sulfide solid electrolyte material and a preparation method thereof. Background Art

[0002] Lithium-ion secondary batteries play an extremely important role in modern society, especially the development of new energy vehicles and large-scale energy storage, which has pushed them to an unprecedented height. With the continuous improvement of the energy density and safety requirements of power batteries, the existing liquid lithium-ion battery system has approached the upper limit of energy density, and the flammable organic electrolyte makes the safety hazards of high-energy liquid lithium-ion batteries more prominent. All-solid-state batteries that use non-flammable inorganic solid materials as electrolytes can not only eliminate the safety hazards caused by organic electrolyte leakage and thermal runaway inside the battery during use, but also can be used under extreme conditions such as high and low temperatures. The use of lithium metal negative electrodes will also further improve the energy density of all-solid-state lithium secondary batteries. Solid electrolytes are the most critical materials in all-solid-state batteries. The development of inorganic solid electrolytes with high stability and high lithium ion conductivity is the key to the development of high-performance all-solid-state batteries.

[0003] Among many solid electrolyte materials, sulfide solid electrolytes are currently the most studied and have the greatest application potential. The main reason is that sulfide electrolytes have ion conductivity comparable to that of liquid electrolytes, but the ion conductivity of sodium ion sulfide electrolytes is generally low. Chinese patent CN115692830A reports a Na ion sulfide solid electrolyte material, whose maximum ion conductivity is only 1.02mS / cm, which is lower than the common lithium ion sulfide solid electrolyte material, and it is difficult to meet the use requirements of all-solid-state batteries. Chinese patents CN112563565B and CN115693032A respectively report a sodium oxide-lithium composite solid electrolyte, and the ion conductivity reported in CN112563565B is even lower, only 0.81mS / cm. The essence of the report in CN115693032A is a diaphragm for liquid batteries, and the use of the intermediate organic layer will inevitably reduce the ionic conductivity of the material. The use of organic matter is also not conducive to improving the safety performance of all-solid-state batteries. Chinese patent CN115189014A reports an inorganic sulfide-organic composite solid electrolyte, but the organic electrolyte with low ionic conductivity reduces the ionic conductivity of the sulfide electrolyte, and the preparation process of the organic electrolyte is complicated, there is a risk of organic solvent contamination, and the organic electrolyte has poor thermal stability, which is not conducive to improving the safety performance of solid-state batteries.

[0004] Therefore, it is necessary to develop a high ion conductivity lithium-sodium composite inorganic sulfide electrolyte material to meet the practical use requirements of all-solid-state batteries. Summary of the invention

[0005] In order to solve the above technical problems of the present invention, the present invention provides a lithium-sodium composite inorganic sulfide solid electrolyte material and a preparation method thereof, so as to solve the problem of low ion conductivity of existing inorganic sulfide solid electrolyte materials.

[0006] According to the first aspect of the present invention, the present invention provides a lithium-sodium composite inorganic sulfide solid electrolyte material, the composition of which is shown in the following general formula I:

[0007] Li 7-i-k-l Na i P j S k X1 (I);

[0008] Wherein, X is one or more of F, Cl, Br, and I, 0.0<i<7.0, 0.0<j≤1.0, 3.0<k≤6.5, and 0.0≤1<2.0.

[0009] In the above scheme, the present invention has found that when a small amount of Na element is added to the lithium ion solid electrolyte, since the radius of Na ion is larger, it can play a supporting role in the Li ion transmission path, widen the Li ion transmission channel, increase the Li ion transmission speed, and improve the ionic conductivity of the target electrolyte material. By adjusting the types and proportions of elements in the inorganic sulfide solid electrolyte material, a variety of different types of lithium sodium composite inorganic sulfide solid electrolyte materials with solid solution phase structures are obtained. The obtained lithium sodium composite inorganic sulfide solid electrolyte material has a higher ionic conductivity, which can further realize the application of sulfide solid electrolyte materials in high-performance all-solid-state batteries.

[0010] According to the second method of the present invention, the present invention also provides a method for preparing the above-mentioned lithium-sodium composite inorganic sulfide solid electrolyte material, comprising the following steps:

[0011] Step (1): under the protection of an inert atmosphere, the required raw materials are mixed according to a proportion and then ground;

[0012] Step (2): heat-treating the ground material under an inert atmosphere.

[0013] In the above scheme, the preparation method of the lithium-sodium composite inorganic sulfide solid electrolyte material is to first mix the required raw materials according to the ratio under the protection of an inert atmosphere and then grind them to achieve a suitable fineness value, and mix the raw materials fully, which is conducive to obtaining a solid electrolyte with high ionic conductivity after subsequent heat treatment, and then the ground material is heat treated under the protection of an inert atmosphere to remove volatile substances and moisture in the raw materials, improve the density and mechanical strength of the raw materials, improve the ionic conductivity of the raw materials, and at the same time improve the chemical stability of the materials.

[0014] Furthermore, in step (1), the grinding is carried out in a ball mill, the grinding linear speed v is 7.5 m / s to 16.0 m / s, and the time t is 3 h to 24 h.

[0015] The applicant has found that the synthesis conditions of Li-Na composite solid electrolytes are very harsh, otherwise the target electrolyte material with high ion conductivity cannot be obtained. In the above scheme, by limiting the linear speed and time of grinding within a reasonable range, it is beneficial to improve the grinding efficiency, which is more conducive to preparing a lithium-sodium composite inorganic sulfide solid electrolyte material with high ion conductivity.

[0016] Furthermore, in step (1), 5.0E+05m≤v×t≤7.0E+05m.

[0017] In the above scheme, by limiting the value of v×t within a reasonable range, it is more conducive to improving the grinding efficiency, thereby being more conducive to preparing a lithium-sodium composite inorganic sulfide solid electrolyte material with high ionic conductivity.

[0018] Further, in step (1), 5.0+0.2i≤(v×t)E+05≤5.5+0.2i.

[0019] In the above scheme, by limiting the relationship between the value of v×t and i within a reasonable range, it is more conducive to improving the grinding efficiency, thereby being more conducive to preparing a lithium-sodium composite inorganic sulfide solid electrolyte material with high ionic conductivity.

[0020] Furthermore, in step (2), the heat treatment temperature T is 500°C-750°C, and the heat treatment time is 20h-48h.

[0021] In the above scheme, by limiting the temperature and time of the heat treatment within a reasonable range, it is more conducive to preparing a lithium-sodium composite inorganic sulfide solid electrolyte material with high ionic conductivity.

[0022] Further, in step (2), 440+150i 1 / 3 ≤T≤450+155i 1 / 3 .

[0023] In the above scheme, by limiting the relationship between the value of T and i within a reasonable range, it is more conducive to preparing a lithium-sodium composite inorganic sulfide solid electrolyte material with high ionic conductivity.

[0024] According to the third aspect of the present invention, the present invention also provides a lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, wherein the solid electrolyte layer contains the above-mentioned lithium-sodium composite inorganic sulfide solid electrolyte material, or the lithium-sodium composite inorganic sulfide solid electrolyte material prepared by the above-mentioned preparation method.

[0025] The technical solution provided by the present invention has the following beneficial effects:

[0026] The present invention discloses a lithium-sodium composite inorganic sulfide solid electrolyte material. The types and proportions of elements in the material are adjusted to obtain lithium-sodium composite inorganic sulfide solid electrolyte materials of various types with solid solution phase structures. The obtained lithium-sodium composite inorganic sulfide solid electrolyte material has higher ionic conductivity, and can further realize the application of sulfide solid electrolyte materials in high-performance all-solid-state batteries.

[0027] The lithium-sodium composite inorganic sulfide solid electrolyte material of the present invention is helpful for further understanding the problem of improving the ion conductivity of the lithium-sodium composite inorganic sulfide solid electrolyte material in theoretical research, and can obtain a variety of different types of high-performance electrolyte materials in practical application, which is helpful to solve the practical application problem of inorganic sulfide electrolytes as high-performance all-solid-state lithium secondary battery electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 is an X-ray diffraction pattern of the solid electrolyte material obtained in Example 8;

[0030] Figure 2 This is a SEM image of the solid electrolyte material obtained in Example 8;

[0031] Figure 3 This is the EIS spectrum of the solid electrolyte material obtained in Example 8. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the present invention, if no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased through regular channels.

[0034] Comparative Example 1-2

[0035] The preparation was carried out according to the method reported in patent CN115692830A.

[0036] Comparative Examples 3-5, Examples 1-15

[0037] In a glove box, weigh Li2S, Na2S, P2S5, and LiCl according to the element ratio in Table 1, place the above raw materials in a 50ml zirconium oxide ball mill, and add 50g of 5mm diameter zirconium oxide balls. Place the sealed ball mill on the ball mill, set the speed and time according to the parameters in Table 1 for ball milling. Collect the ball-milled samples, seal them in a vacuum quartz tube, and calcine them according to the temperature in Table 1. The calcination temperature is controlled by program temperature rise, and the temperature is naturally lowered to 50°C after sintering to obtain the target solid electrolyte material.

[0038] Figure 1 This is the X-ray diffraction diagram of the solid electrolyte material obtained in Example 8. It can be seen that the diffraction peak of the solid electrolyte material is sharp, indicating that its crystallinity is high.

[0039] Figure 2 This is a SEM image of the solid electrolyte material obtained in Example 8. It can be seen that the prepared electrolyte material has clear particle boundaries and good crystallinity.

[0040] Figure 3 This is the EIS spectrum of the solid electrolyte material obtained in Example 8, based on which the ionic conductivity is calculated to be 6.37 mS / cm.

[0041] Table 1 Composition and ion conductivity data of comparative examples 1 to 5 and embodiments 1 to 15

[0042]

[0043] Table 1 summarizes the composition and ion conductivity performance data of comparative examples 1 to 5 and embodiments 1 to 15. The experimental results of embodiments 1 to 15 show that the inorganic sulfide solid electrolyte material provided by the present invention has a high ion conductivity of more than 2.0 mS / cm, among which the inorganic sulfide solid electrolyte material of embodiment 8 has the highest ion conductivity of 6.37 mS / cm. It can be seen from the comparison results of the embodiments that during the preparation process, the value of v×t, the heat treatment temperature T and the Na element ratio i in the material meet the following conditions: 5.0+0.2i≤(v×t)E+05≤5.5+0.2i, 440+150i 1 / 3 ≤T≤450+155i 1 / 3 When the ion conductivity of the material is improved.

[0044] It can be seen from the experimental comparison results of Comparative Examples 1-2 and Example 8 that the inorganic sulfide solid electrolyte material prepared by the specific components and the specific preparation method of the present invention has high ion conductivity characteristics. It can be seen from the experimental comparison results of Comparative Examples 3-5 and Example 8 that controlling the ratio between Li, Na, P, S, and Cl within a specific range of values ​​can enable better synergistic effects between the elements, which is more conducive to improving the ion conductivity of the material.

[0045] The inorganic sulfide solid electrolyte material provided by the present invention has a simple composition, readily available raw materials, a simple preparation method, low production cost, and high ion conductivity, and is expected to solve the practical application problem of inorganic sulfide electrolytes as high-performance all-solid-state lithium secondary battery electrolytes.

[0046] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-sodium composite inorganic sulfide solid electrolyte material, characterized in that: Its composition is shown in the following general formula I: Li 7-i-l So i Q j S k X l (I); Wherein, X is one or more of F, Cl, Br, and I, 0.0 <i<7.0,0.0<j≤1.0,4.0≤k≤4.2,l=1.8; The preparation method of the lithium-sodium composite inorganic sulfide solid electrolyte material comprises the following steps: Step (1): under the protection of an inert atmosphere, the required raw materials are mixed according to a proportion and then ground; Step (2): heat treating the ground material under an inert atmosphere; In step (1), the grinding is carried out in a ball mill, the grinding linear speed v is 7.5 m / s to 16.0 m / s, and the time t is 3 h to 24 h; In step (1), 5.0E+05m≤v×t≤7.0E+05m; In step (1), 5.0+0.2i≤(v×t)E+05≤5.5+0.2i; In step (2), the heat treatment temperature T is 500°C-750°C, and the heat treatment time is 20h-48h; In step (2), 440+150i 1 / 3 ≤T≤450+155i 1 / 3 .

2. A lithium secondary battery, characterized in that: It comprises a positive electrode layer, a negative electrode layer and a solid electrolyte layer, wherein the solid electrolyte layer contains the lithium-sodium composite inorganic sulfide solid electrolyte material according to claim 1.

Citation Information

Patent Citations

  • A method for preparing a lithium-sodium ion hybrid solid electrolyte and a solid hybrid battery

    CN112563565B

  • Preparation and application of composite electrolyte membrane based on sodium ion sulfide solid electrolyte

    CN115189014A

  • Sodium ion sulfide electrolyte and preparation method thereof

    CN115692830A

  • Sodium-lithium composite solid electrolyte diaphragm, preparation method and sodium-lithium composite battery

    CN115693032A

  • Solid-state battery cell, preparation method thereof and solid-state lithium ion battery

    CN116315055A